2020
DOI: 10.1080/07317115.2020.1751765
|View full text |Cite
|
Sign up to set email alerts
|

Race and Personal Exposure to AD Influence Projected Memory Failure Attributions and Help-Seeking Behaviors

Abstract: Objective: Examine race and personal exposure to Alzheimer's Disease (AD) on projected memory failure attributions and medical help-seeking thresholds of pre-morbid adults. The goal is to better understand race discrepancies in help-seeking for those potentially at risk for early-onset AD. Methods: 498 adults aged 40 to 65 (M = 52.27), screened for current memory failure, completed an online questionnaire exploring their help-seeking intentions and threshold, attributions of hypothetical memory failures, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Similarly, the relationship between dementia exposure and dementia worry is unclear. Some studies have found that individuals who have relatives with AD or dementia are more concerned about potential signs and symptoms of cognitive impairment ( Hodgson & Cutler, 2003 ), and may be more likely to attribute memory problems to potential cognitive impairment ( Mills et al, 2023 ). In contrast, other studies have found no relationship between dementia exposure and dementia worry (e.g., French, 2008 ), while evidence of dementia worry among those without any exposure perhaps suggests a “fear of the unknown” (e.g., Cutler & Hodgson, 2001 ; Kessler et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the relationship between dementia exposure and dementia worry is unclear. Some studies have found that individuals who have relatives with AD or dementia are more concerned about potential signs and symptoms of cognitive impairment ( Hodgson & Cutler, 2003 ), and may be more likely to attribute memory problems to potential cognitive impairment ( Mills et al, 2023 ). In contrast, other studies have found no relationship between dementia exposure and dementia worry (e.g., French, 2008 ), while evidence of dementia worry among those without any exposure perhaps suggests a “fear of the unknown” (e.g., Cutler & Hodgson, 2001 ; Kessler et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%